1999
DOI: 10.1097/00007632-199901010-00013
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Muscle Weakness as a Risk Factor for Low Back Pain

Abstract: An imbalance in trunk muscle strength, i.e., lower extensor muscle strength than flexor muscle strength, might be one risk factor for low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
138
0
19

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(164 citation statements)
references
References 17 publications
7
138
0
19
Order By: Relevance
“…A cohort study evaluated 215 Portuguese schoolchildren concluded that low levels of muscle strength of the trunk extensors/flexors were associated with a higher prevalence of low back pain and low flexibility of the posterior thigh muscles 10 . Similar results were found in another study 9 .…”
supporting
confidence: 92%
See 2 more Smart Citations
“…A cohort study evaluated 215 Portuguese schoolchildren concluded that low levels of muscle strength of the trunk extensors/flexors were associated with a higher prevalence of low back pain and low flexibility of the posterior thigh muscles 10 . Similar results were found in another study 9 .…”
supporting
confidence: 92%
“…In addition, studies indicate that female and adolescents with inadequate lifestyle habits such as physical inactivity, sedentary behavior and overweight are the subgroups vulnerable to frequent low back complaints among adolescents 5,6 . Surveys have shown that another possible cause of low back pain is associated with low levels of lumbar force [7][8][9] . A cohort study evaluated 215 Portuguese schoolchildren concluded that low levels of muscle strength of the trunk extensors/flexors were associated with a higher prevalence of low back pain and low flexibility of the posterior thigh muscles 10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired motor control may promote chronicity or recurrent LBP and even be a risk factor for LBP [37,38]. From this perspective, it has been suggested that people with mild deficits of the central nervous system [21], such as an imbalance in recruitment of agonist and antagonist trunk muscles [28,36], slow reaction times [49] or poor proprioception [39], are at risk of developing musculoskeletal disorders. The motor functioning of individuals with LBP is complicated further by the fact that, whereas walking more quickly with impaired coordination may enhance the mechanical instability of the spine, walking more slowly may have considerable disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…The core stability is essential to prevent injuries (10,20) and improve performance in athletes. Weak core muscles may be a risk factor for low back pain (9). Zazulak et al (21) reported that trunk displacement was greater in athletes with knee and ACL injuries compared with uninjured athletes.…”
Section: Introductionmentioning
confidence: 99%